State Resolved Measurements of Surface Temperature Dependence and Isotopically Selective Reactivity of Methane on Ni(111). - Campbell, Victoria. (2017)
Abstract: Eigenstate-resolved molecular beam experiments are particularly useful at partitioning internal energy within a gas molecule and probing the effect of this energy on reactivity. This is chiefly useful because the inherent nature of molecular beams tends to convolute translational, rotational and vibrational energy and their respective effects on reactivity. Methane reactivity on catalytic surfaces is of interest because of its industrial significance. The cleavage of the C-H bond is the rate-limiting step during reaction and better understanding the dynamics of this process can be useful industrially. This thesis will extensively explore the role surface phonons play in promoting reactivity of methane on a Ni(111) surface. There will be a comprehensive overview of the impact of surface temperature dependence on reactivity under different beam conditions, surface temperatures and in the presence of IR irradiation. There has been some previous experimental work performed looking for some surface temperature dependence for CH4 reacting on Ni(111). However, in most cases, these experiments were performed in energy rich regimes, which effectively "masked" some of the more subtle surface temperature effects. These experiments also sampled reactivity with contributions from translational, rotational and vibrational contributions. Theory has demonstrated that there should be an energetic threshold to reaction but the convoluted nature of molecular beam experiments has made this unobservable in gas surface reactions. The work in this thesis combines the use of supersonically expanded molecular beams, state specific IR irradiation and variance in surface temperature to show for the first time an energetic threshold to reaction in a gas-surface reaction. This thesis also includes isotope selective chemical vapor deposition using vibrational activated methane. These experiments use narrow bandwidth IR to selectively excite the 12CH4 and 13CH4 isotopologues and control the ratio of carbon isotopes that get deposited on the Ni(111) surface. The use of the laser allows for the isotopic control and separation to occur in one step, as opposed to some of the iterative processes isotope selectivity usual requires. The last chapter focuses on the development of a new detection technique that utilizes King & Wells experimental technique with lock-in devices. The main premise behind this new detection scheme is to couple the K&W experiments and the lock-in detection method in hopes of developing a more sensitive method capable of making quick, easy measurements in a lower sticking regime.; Thesis (Ph.D.)--Tufts University, 2011.; Submitted to the Dept. of Chemistry.; Advisor: Arthur Utz.; Committee: Mary Jane Shultz, Jonathan Kenny, and Bret Jackson.; Keyword: Physical chemistry.